2007
DOI: 10.1155/2007/941618
|View full text |Cite
|
Sign up to set email alerts
|

Complete Disappearance of Lung Abnormalities on High‐Resolution Computed Tomography: A Case of Histiocytosis X

Abstract: A case of pulmonary Langerhans cell histiocytosis, proved by both lung high-resolution computed tomography and lung biopsy, is described. Following smoking cessation, lung nodules and cysts gradually disappeared on serial computed tomography scans, with complete clearance of the lesions after 12 months. The role of tobacco smoking is discussed, in detail, against the background of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…While the course of pulmonary LCH in adults is variable and unpredictable, ranging from spontaneous regression to progressive relentless disease leading to respiratory failure and death over a period of months, 5-year survival is 74.6-87.8% (6,8). In most patients, especially those who are asymptomatic in the early stage of isolated pulmonary LCH, smoking cessation without other treatment interventions can improve or maintain clinical and radiographic findings with regard to pulmonary involvement (11,12). Although bone lesions are the most common extrapulmonary involvement in multisystem pulmonary LCH in adults, little information is known about their appropriate management (3,(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…While the course of pulmonary LCH in adults is variable and unpredictable, ranging from spontaneous regression to progressive relentless disease leading to respiratory failure and death over a period of months, 5-year survival is 74.6-87.8% (6,8). In most patients, especially those who are asymptomatic in the early stage of isolated pulmonary LCH, smoking cessation without other treatment interventions can improve or maintain clinical and radiographic findings with regard to pulmonary involvement (11,12). Although bone lesions are the most common extrapulmonary involvement in multisystem pulmonary LCH in adults, little information is known about their appropriate management (3,(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of LCH is still unknown [6], although there are some theories which have grown from the research conducted over the past few years. However, there is evidence that Langerhans cell proliferations represent a spectrum of disease that ranges from reactive to neoplastic phenomenon [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Although in children chemotherapy with vinblastine and prednisone proved to be effective, the results of treatment in adults turned out to be less successful [3,[7][8][9][10][11][12][13][33][34][35][36][37][38][39][40][41]. In patients with multiple bone lesions and affected lungs, significantly higher effectiveness of treatment with cytarabine or cladribine compared to vinblastine and prednisone has been shown.…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…It has been shown that PLCH patients have lower mean survival compared to people of the same sex and age [8]. Approximately 50% of patients experience spontaneous regression of the disease with improvement or stabilisation of the ventilation parameters only after smoking cessation [3,29,32,34]. In the remaining cases, the disorder gradually progresses, both in the lungs and in other organs.…”
Section: Prognosismentioning
confidence: 99%